A modified reconstructive technique for paediatric congenital alar rim deformity. (March 2019) - Ujam, Atheer B.; Bulstrode, Neil W.
Abstract: Alar subunit retraction or notching whether acquired or congenital, can be challenging to reconstruct. Congenital cysts and benign lumps involving the nasal alar region can also result in acquired alar deformity once resected. Published reports describe different surgical methods, but we demonstrate a simple and highly satisfying technique. We present four paediatric cases with alar rim defects and demonstrate our modified surgical technique. All patients had an unremarkable recovery. Our outcomes demonstrate a minimal yet effective one-stage technique for correction of alar defects in paediatric patients that results in high patient satisfaction and allows for future secondary surgery if required.